Prevalence of dyslipidemia and associated risk factors among newly diagnosed Type-2 Diabetes Mellitus (T2DM) patients in Kushtia, Bangladesh. - Md Saad Ahmmed; Suvasish Das Shuvo; Dipak Kumar Paul; M R Karim; Md Kamruzzaman; Niaz Mahmud; Md Jannatul Ferdaus; Md Toufiq Elahi (Public Library of Science (PLoS), 2021)
Dyslipidemia is considered a significant modifiable risk factor for type-2 diabetes mellitus (T2DM) and has become one of the emerging health problems throughout the world. In Bangladesh, data on dyslipidemia among newly diagnosed T2DM patients are comparatively inadequate. This study aimed to evaluate the prevalence of dyslipidemia and its associated risk factors in newly diagnosed T2DM patients. This cross-sectional study was conducted by a well-structured questionnaire from 132 newly diagnosed type-2 diabetic patients attending the Mujibur Rahman Memorial Diabetic Hospital in Kushtia, Bangladesh. Data regarding socio-demographic, anthropometric, fasting blood glucose, total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) were collected from all the respondents. The association between dyslipidemia and its associated factors was analyzed using the multivariate logit regression model. The findings suggest that the prevalence rate of dyslipidemia was 75.7% in female and 72.6% in male T2DM patients. The odds of having dyslipidemia were 1.74 (95% Cl: 1.58-1.87) times significantly higher in female (p<0.001). The other factors associated with dyslipidemia encompassed age between 30-39 years (OR: 2.32, 95% CI: 1.97-2.69), obesity (OR: 2.63, 95% CI: 2.27-2.90), waist circumferences of male ≥90 and female ≥80 (OR: 1.65, 95% CI: 1.59-1.89), hypertensive patients (OR: 1.51, 95% CI: 1.45-1.74), physically inactive (OR: 3.25, 95% CI: 1.84-4.68), and current smoker or tobacco user (OR: 1.93, 95% CI: 1.85-2.13). This study concluded that the high prevalence of dyslipidemia was found among newly diagnosed type-2 diabetes patients and associated with gender, age, BMI, waist circumference, poor physical activity, and smoking, or tobacco use. This result will support increase awareness of dyslipidemia and its associated risk factors among type-2 diabetes patients.